Menuju kesejahteraan dalam masyarakat hutan: buku panduan untuk pemerintah daerah (Center for International Forestry Research, 2007)
Governments in many countries are decentralising to give more control over decision making and budgets to local administrations. One expectation of this change is that local governments will more effectively and efficiently respond to the poorest citizens in their jurisdictions. Decentralisation is especially significant to forest communities, which have historically benefited little from government services and poverty reduction programmes because of their physical isolation and social marginalisation. This Source Book was written for local governments and their partners who hope to respond to the needs of forest communities and improve the wellbeing of their people. It first discusses important concepts, such as decentralisation, wellbeing, poverty and the link between forests and poverty. It then presents four participatory tools that local governments may find useful to involve forest communities in the planning, monitoring and evaluation of development and poverty alleviation programmes, namely: monitoring local poverty contexts through interactive mapping; monitoring household wellbeing through local indicators; community evaluation of local government programmes; and communicating communities’ needs through scenario-based planning. The Source Book is based on the findings of an action research project carried out in forest communities in Indonesia and Bolivia by the Center for International Forestry Research (CIFOR). Although developed and tested in just two countries, the concepts and tools apply to people and governments around the globe.